VCMA Gradient-Driven Skyrmion on a Trapezoidal Nanotrack for Racetrack Memory Application - Bikash Sharma; Pema Rinzing Bhutia; Ravish Kumar Raj; Bibek Chettri; Brajesh Kumar Kaushik; Sonal Shreya (IEEE Open Journal of Nanotechnology)
Magnetic skyrmion has great potential as information carriers in next-generation logic, neuromorphic computing, and memory devices because of its topological stability, incredibly compact size, and low current consumption required to operate it. In this work, the computational demonstration of a skyrmion controlled by a voltage controlled magnetic anisotropy (VCMA) gradient on a trapezoidal nanotrack is studied for the application of racetrack memory. The trapezoidal nanotrack aids in guiding the skyrmion's motion under the anisotropy gradient by leveraging the edge repulsion force. By utilizing a defect, the proposed device ensures a continuous flow of binary bits ‘0’ and ‘1’ without any accumulation on the racetrack. The higher angle (θhigh) and higher anisotropy gradient (ΔKu-high) of the trapezoidal nanotrack accelerates the skyrmion owing to higher edge repulsion force and energy gradient force. The maximum speed of 1.27 m/s was achieved by the skyrmion, and the minimum time taken for the skyrmion to reach the detector from the nucleation point was 2.16 ns. The energy used to maintain the electric field is 4.58fJ per bit operation. This presents a novel approach to manipulate skyrmions under anisotropy gradient (ΔKu) on the trapezoidal nanotrack, paving the way for the development of improved skyrmion racetrack memory (sk-RM).